Assessing Senior Managers\' Level of Awareness of Standards and Regulations Related to the Health System: A Case Study in Tehran University of Medical Sciences - Hossein Dargahi; Farugh Nomani; Mohammad Rahim Ghohestani (Tehran University of Medical Sciences, 2021)
Background and Aim: Managers' sufficient awareness about rules and regulations and the legal issues of health system may lead to their optimal performance in organizations. Therefore, this study is conducted to determine senior managers' level of knowledge about legal rules and regulations related to the health system in Tehran University of Medical Sciences (TUMS). Materials and Methods: The present descriptive-analytical cross-sectional study was conducted in 2017. The sample consisted of 75 senior managers. The research tool was a researcher-made questionnaire whose face validity was confirmed using the opinions of 7 specialists and experts in the field of medical law, health care and medical services management; besides, regarding its reliability, Cronbachchr('39')s alpha and test-retest reliability coefficients were 0.89 and 0.79, respectively. With SPSS software, data analysis was performed using descriptive statistics including absolute and relative frequency and inferential statistics including Pearson and Ka-square correlation tests. Results: The level of knowledge of the studied managers was below average in most legal areas and legal standards related to the health system. There was a significant inverse relationship between the level of knowledge of organizational, financial and transactional areas, and administrative and employment of managers with passing relevant training courses (P=0.01 and P=0.04). Conclusion: TUMS senior managerschr('39') level of knowledge in the three areas of organizational, financial, and rules and regulations is at medium and lower than medium levels. To raise the awareness of managers, necessary arrangements such as holding training courses with new methods such as simulation, screenwriting, case study and experimentation and using new technologies such as hybrid knowledge management and technology integration are suggested. Also, creating managerschr('39') strategic competency system at the levels of general and specific skills, along with continuous training and monitoring the accountability and feedback provided in management processes, will ensure future reforms.